Effects of concentrated growth factor and nanofat on aging skin of nude mice induced by D-galactose - Sun, W; Li, T; Yao, H; Kang, L; Dong, F (Physiological research, 2021)
This investigation studied the effect of concentrated growth factor and nanofat on aging skin of nude mice induced by D-galactose. BALB/c mice were randomly divided into five groups: 5 mice in the control group were fed normally without any intervention, 9 mice were treated with concentrated growth factor (CGF), 9 mice were treated with nanofat (NF), 9 mice were treated with CGF+NF, and 9 mice in the model group (no treatment after subcutaneous injection of D-galactose). Relevant indicators are measured and recorded. In skin and serum, SOD and GSH content in the model group were significantly lower than those in other groups (P<0.05), and the MDA of the three treatment groups was significantly lower than that of the model group (P<0.05). Compared with the control group, the contents of total collagen, type I collagen and type III collagen in the NF group and model group were decreased in different degrees (P<0.05); the contents of elastin and elastic fiber in the skin of nude mice in the model group and NF group were significantly decreased. Compared with the model group, he number of CD31 and VEGF in the treatment group was significantly increased (P<0.01); the skin AGE content of three treatment groups was significantly lower (P<0.05). These findings suggest that concentrated growth factor and nanofat may have a significant effect on delaying aging skin induced by D-galactose in nude mice.
Keywords: Male; Skin Aging; tuková tkáň; myši nahé; myši inbrední BALB C; galaktosa; Galactose; kolagen; mužské pohlaví; antigeny CD31; Mice, Inbred BALB C; Elastin; glutathion; stárnutí kůže; Intercellular Signaling Peptides and Proteins; Animals; Adipose Tissue; mezibuněčné signální peptidy a proteiny; zvířata; Collagen; myši; Platelet Endothelial Cell Adhesion Molecule-1; Glutathione; elastin; vaskulární endoteliální růstový faktor A; Vascular Endothelial Growth Factor A; Superoxide Dismutase; Mice, Nude; Mice; superoxiddismutasa